1999
DOI: 10.1097/00005392-199904020-00570
|View full text |Cite
|
Sign up to set email alerts
|

C-11 Acetate Pet Imaging of Prostate Cancer

Abstract: C-Acetate can act as a probe of tissue metabolism through entry into catabolic or anabolic metabolic pathways as mediated by acetyl-coenzyme A. The uptake of 11 C-acetate in prostate cancer was investigated to determine whether this tracer has potential in tumor identification. Methods: Twenty-two patients with prostate cancer underwent PET after intravenous administration of 740 MBq 11 C-acetate. Eighteen of the 22 patients were also investigated with 18 F-FDG PET. Standardized uptake values (SUVs) for each t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
171
0
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(181 citation statements)
references
References 19 publications
4
171
0
6
Order By: Relevance
“…The acetate uptake in our subgroups was similar to those of Oyama et al (6) for primary cancer, ranging from 3.3 to 9.9 SUV, compared with our 1.8-5.5 SUV. The higher numbers suggest more advanced disease in their population.…”
Section: Prostate Cancer Kinetics and Biologysupporting
confidence: 91%
See 1 more Smart Citation
“…The acetate uptake in our subgroups was similar to those of Oyama et al (6) for primary cancer, ranging from 3.3 to 9.9 SUV, compared with our 1.8-5.5 SUV. The higher numbers suggest more advanced disease in their population.…”
Section: Prostate Cancer Kinetics and Biologysupporting
confidence: 91%
“…In 6 of 10 men with recurrent cancer, the PSA velocity was ,0.3 mg/mL/mo. Oyama et al (6) also found a relation between age and uptake. We had only 2 patients younger than 50-y-old.…”
Section: Prostate Cancer Kinetics and Biologymentioning
confidence: 89%
“…Sensitivity was 100% for 11 C-acetate (no accumulation in the urine) and 83% with 18 F-FDG (due to tracer retention in the bladder). 44 The relatively high proportion of 18 F-FDG prostate positivity in this study was explained by the advanced stage of the majority of cases.…”
Section: Methodological Issues Regarding the Assessment Of Locally Rementioning
confidence: 60%
“…Oyama et al 44 compared 11 C-acetate to 18 F-FDG in a small patient cohort with biopsy-proven and mostly locally advanced prostate cancer. Sensitivity was 100% for 11 C-acetate (no accumulation in the urine) and 83% with 18 F-FDG (due to tracer retention in the bladder).…”
Section: Methodological Issues Regarding the Assessment Of Locally Rementioning
confidence: 99%
“…It is interesting to note that as shown by small animal PET studies in rat prostate and prostate cancer models [32], androgen stimulation leads to increased 18 F-FDG uptake, indicating probable acceleration of the glucose-pyruvate-malate cycle, whilst 11 C-acetate uptake was not affected by androgen treatment.…”
Section: Prostate Metabolism In Manmentioning
confidence: 88%